Effects of carbon sources on sludge performance and microbial community for 4-chlorophenol wastewater treatment in sequencing batch reactors. (May 2018) - Zhao, Jianguo; Li, Yahe; Chen, Xiurong; Li, Yu
Highlights: The sludge performance and microbial community for 4-CP treatment were investigated. The removal efficiencies of various pollutants were not influenced by carbon sources. The microbial diversity was influenced by different carbon sources at various levels. The EPS formation in sludge was related to microbial communities. Abstract: Considering carbon sources are often supplied to satisfy the removal of high nitrogen and refractory pollutants in industrial wastewater, two sequencing batch reactors (SBRs) were used in this study to treat 1.5 ± 0.5 mg/L 4-chlorophenol (4-CP) wastewater containing ammonium nitrogen and phosphate with different carbon sources. The favorable removal efficiencies of influent COD, NH4 + -N, PO4 3− -P, and 4-CP suggested that the both SBRs were not influenced by supplying dissolved starch and sodium acetate, respectively. The phyla Proteobacteria and Bacteroidetes were dominant in both SBRs, while the dominant phylum Candidatus Saccharibacteria was only existed in SBR with carbon source of dissolved starch. The relative abundance of bacterial communities had significant differences at class, family, and order level in both SBRs. And the mutually dominant genus in both SBRs was only Gemmobacter, which was first found in 4-CP wastewater treatment. The changed extracellular polymeric substances (EPS) were related with microbial communities.